2021
DOI: 10.1093/pubmed/fdaa267
|View full text |Cite
|
Sign up to set email alerts
|

Complex differences in infection rates between ethnic groups in Scotland: a retrospective, national census-linked cohort study of 1.65 million cases

Abstract: Background Ethnicity can influence susceptibility to infection, as COVID-19 has shown. Few countries have systematically investigated ethnic variations in infection. Methods We linked the Scotland 2001 Census, including ethnic group, to national databases of hospitalizations/deaths and serological diagnoses of bloodborne viruses for 2001–2013. We calculated age-adjusted rate ratios (RRs) in 12 ethnic groups for all infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Funding sources were not declared for 35 (35%) of reports. The Scottish Government funded 20 reports (20%) [ 13 , 27 , 32 , 39 , 45 – 47 , 66 , 77 , 88 , 99 – 102 , 113 , 116 , 119 , 121 , 129 , 134 ]. Other common sources of funding included Government funded public bodies ( n = 13) [ 45 , 48 53 , 104 , 107 , 113 , 116 , 131 , 136 ], the Scottish Health Service ( n = 18) (either the National Health Service (NHS) [ 13 , 54 , 56 – 59 , 102 , 113 , 116 ], local NHS trusts [ 45 , 60 , 61 , 77 , 102 , 103 , 112 ] or by Public Health Scotland [ 13 , 113 ]) Eleven reports (11%) were funded by Universities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Funding sources were not declared for 35 (35%) of reports. The Scottish Government funded 20 reports (20%) [ 13 , 27 , 32 , 39 , 45 – 47 , 66 , 77 , 88 , 99 – 102 , 113 , 116 , 119 , 121 , 129 , 134 ]. Other common sources of funding included Government funded public bodies ( n = 13) [ 45 , 48 53 , 104 , 107 , 113 , 116 , 131 , 136 ], the Scottish Health Service ( n = 18) (either the National Health Service (NHS) [ 13 , 54 , 56 – 59 , 102 , 113 , 116 ], local NHS trusts [ 45 , 60 , 61 , 77 , 102 , 103 , 112 ] or by Public Health Scotland [ 13 , 113 ]) Eleven reports (11%) were funded by Universities.…”
Section: Resultsmentioning
confidence: 99%
“…The Scottish Government funded 20 reports (20%) [ 13 , 27 , 32 , 39 , 45 – 47 , 66 , 77 , 88 , 99 – 102 , 113 , 116 , 119 , 121 , 129 , 134 ]. Other common sources of funding included Government funded public bodies ( n = 13) [ 45 , 48 53 , 104 , 107 , 113 , 116 , 131 , 136 ], the Scottish Health Service ( n = 18) (either the National Health Service (NHS) [ 13 , 54 , 56 – 59 , 102 , 113 , 116 ], local NHS trusts [ 45 , 60 , 61 , 77 , 102 , 103 , 112 ] or by Public Health Scotland [ 13 , 113 ]) Eleven reports (11%) were funded by Universities. The charity sector financed 15 (15%) reports [ 53 , 63 , 66 , 69 – 74 , 103 , 111 , 123 , 125 , 132 , 138 ] and the EU and Scottish local authorities funded four reports each [ 45 , 62 , 75 – 77 , 102 , 125 , 135 ].…”
Section: Resultsmentioning
confidence: 99%
“…As previous UK studies have shown, anonymous linkage of the census to health and death records provides a powerful means of exploring the complex relationships between ethnic group, place of birth and health. 39 An expert group in Scotland recently concluded that this type of linkage would provide the most robust and publicly acceptable means of examining the interaction between COVID-19, ethnicity, country of birth and other inter-related factors. 40 Other countries should consider adopting similar methods as well as improve data of migrants within health information systems.…”
Section: Implications For Research Policy and Practicementioning
confidence: 99%
“…We linked data, including data from the census, mortality records,4 hospital admissions databases,5 infection registers,6 cancer registration,7 bowel and breast cancer screening registers,89 electronic general practice and primary care records,10 and the sensitive data of the Mental Welfare Commission for Scotland, including on compulsory admission to psychiatric hospital 11. These linkages won the support of professionals, professional bodies, ethical committees, funders, and the public, and to date there have been no complaints and no data breaches.…”
mentioning
confidence: 99%